Designing Long-Term Care Systems: Elements to Consider - Villalobos-Dintrans, P (Routledge, 2020)
Population aging presents huge challenges for most countries around the world. In this context, long-term care systems appear as a feasible solution to the multidimensional issues arising from demographic change. However, designing a long-term care system is complex. This article presents a structure to analyze long-term care systems based on four components: beneficiaries, benefits, providers, and financing. It uses the experience of three countries to illustrate the many choices available when designing the system, emphasizing the need to understand each component and their interactions. The analysis highlights the existence of several alternatives when designing and implementing long-term care systems. © 2019, © 2019 Taylor & Francis.
Keywords: Long-term care system; system design; health system; social security